The Importance of Syntax in Linguistic Analysis: A Comprehensive Library-Based Review of Theoretical Perspectives - Veriyansah, Veriyansah; Khuailid, Ahmad Ridho; Nasution, Raja Farhan Ansory; Ismahani, Siti (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
Syntax has long occupied a central position in linguistic theory due to its role in explaining how linguistic elements are systematically organized into meaningful structures. While syntax is often introduced as a technical component of grammar concerned with sentence formation, its theoretical significance extends far beyond mechanical rule application. Syntax provides insight into speakers’ implicit grammatical knowledge and serves as a bridge between form, meaning, and language use. Nevertheless, syntactic studies are frequently perceived as abstract and detached from communicative reality, leading to a limited appreciation of their analytical value. This article aims to examine the importance of syntax in linguistic analysis through a comprehensive library-based review of major theoretical perspectives. Employing a qualitative descriptive approach, the study synthesizes key works from structural, generative, functional, and cognitive linguistics. Rather than privileging a single framework, the article adopts an integrative stance, highlighting how different syntactic theories contribute complementary insights into the nature of grammatical structure. The findings of this review indicate that syntax remains indispensable for linguistic explanation. Across theoretical traditions, syntax consistently emerges as a foundational component that shapes interpretation, grammatical relations, and discourse patterns. The study concludes that a pluralistic understanding of syntax offers the most productive approach for contemporary linguistic analysis.